The conquest of Guatemala: a Nahua and Kaqchikel conquest - Solares, Jonathan (The Toro Historical Review, 2020)
Traditionally history has been narrated through a Eurocentric lens and has omitted indigenous perspectives about the Mexican conquests. When learning about the conquest, Iberians have been the main focus of the discussion. However, recent scholars have refocused their attention on indigenous sources that profoundly reshape the historical narrative. As Guatemalan myself, it was not until reading the book Seven Myths of the Spanish Conquests by Matthew Restall that I learned the contributions of indigenous people not only in the conquest of the Mexica Empire but also in the conquest of Guatemala. Acknowledges the contributions of indigenous groups in the conquest of Guatemala, a new approach started by anthropologist Florine G.L. Asselbergs in her book Conquered Conquistadors. This paper seeks to emphasize the agency of indigenous groups in the conquests of Mexico and Guatemala, as the story of their alliance is often ignored and their accomplishments forgotten, as the Iberians’ self-proclaimed superiority has marginalized native contributions.